Tenascin-C May Accelerate Cardiac Fibrosis by Activating Macrophages via the Integrin αVβ3/Nuclear Factor–κB/Interleukin-6 Axis. Issue 4 (October 2015) - Shimojo, Naoshi; Hashizume, Ryotaro; Kanayama, Kazuki; Hara, Mari; Suzuki, Yuka; Nishioka, Tomohiro; Hiroe, Michiaki; Yoshida, Toshimichi; Imanaka-Yoshida, Kyoko
Abstract : Tenascin-C (TN-C) is an extracellular matrix protein not detected in normal adult heart, but expressed in several heart diseases closely associated with inflammation. Accumulating data suggest that TN-C may play a significant role in progression of ventricular remodeling. In this study, we aimed to elucidate the role of TN-C in hypertensive cardiac fibrosis and underlying molecular mechanisms. Angiotensin II was administered to wild-type and TN-C knockout mice for 4 weeks. In wild-type mice, the treatment induced increase of collagen fibers and accumulation of macrophages in perivascular areas associated with deposition of TN-C and upregulated the expression levels of interleukin-6 and monocyte chemoattractant protein-1 as compared with wild-type/control mice. These changes were significantly reduced in TN-C knockout/angiotensin II mice. In vitro, TN-C accelerated macrophage migration and induced accumulation of integrin αVβ3 in focal adhesions, with phosphorylation of focal adhesion kinase (FAK) and Src. TN-C treatment also induced nuclear translocation of phospho-NF-κB and upregulated interleukin-6 expression of macrophages in an NF-κB–dependent manner; this being suppressed by inhibitors for integrin αVβ3 and Src. Furthermore, interleukin-6 upregulated expression of collagen I by cardiac fibroblasts. TN-C may enhance inflammatory responses by accelerating macrophage migration and synthesis of proinflammatory/profibrotic cytokines via integrin αVβ3/FAK-Src/NF-κB, resulting in increased fibrosis. Abstract : Supplemental Digital Content is available in the text.